Shifted equilibria of organic acids and bases in the aqueous surface region. Issue 36 (7th September 2018) - Werner, Josephina; Persson, Ingmar; Björneholm, Olle; Kawecki, Delphine; Saak, Clara-Magdalena; Walz, Marie-Madeleine; Ekholm, Victor; Unger, Isaak; Valtl, Corina; Caleman, Carl; Öhrwall, Gunnar; Prisle, Nønne L.
Abstract : Revealing the delicate balance between protonation/deprotonation and surface/bulk partitioning of organic acids and bases in aqueous solutions. Abstract : Acid–base equilibria of carboxylic acids and alkyl amines in the aqueous surface region were studied using surface-sensitive X-ray photoelectron spectroscopy and molecular dynamics simulations. Solutions of these organic compounds were examined as a function of pH, concentration and chain length to investigate the distribution of acid and base form in the surface region as compared to the aqueous bulk. Results from these experiments show that the neutral forms of the studied acid–base pairs are strongly enriched in the aqueous surface region. Moreover, we show that for species with at least four carbon atoms in their alkyl-chain, their charged forms are also found to be abundant in the surface region. Using a combination of XPS and MD results, a model is proposed that effectively describes the surface composition. Resulting absolute surface concentration estimations show clearly that the total organic mole fractions in the surface region change drastically as a function of solution pH. The origin of the observed surface phenomena, hydronium/hydroxide concentrations in the aqueous surface region and why standard chemical equations, used to describe equilibria in dilute bulk solution are not valid in the aqueous surface region, are discussed in detail. The reported results are of considerable importance especially for the detailed understanding of properties of small aqueous droplets that can be found in the atmosphere.